Bài toán luồng và ứng dụng trong thực tế - Hoa, Vu Dinh; Phuc, Doan; Kha, Dao Dinh (Journal of Computer Science and Cybernetics, 2018)
The algorithm for finding maximal network flows are used for finding solutions of some another problems and one program writing in language basic for the algorithm.